2023
DOI: 10.1021/acs.inorgchem.2c04151
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonium Ylides vs Iminophosphoranes: The Role of the Coordinating Ylidic Atom in cis-[Phosphine-Ylide Rh(CO)2] Complexes

Abstract: The coordinating properties of two families of ylides, namely, phosphonium ylides and iminophosphoranes, differently substituted at the ylidic center (CH2 – vs NiPr–), have been investigated in structurally related cationic phosphine-ylide Rh(CO)2 complexes obtained from readily available phosphine-phosphonium salt precursors derived from an ortho-phenylene bridge. However, while the Rh(CO)2 complex bearing the P+–CH2 – donor moiety proved to be stable, the PNiPr donor end appeared to induce lability to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 100 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The 31 P­{ 1 H}-NMR spectrum of 19 shows the presence of a Rh-coordinated phosphine (δ P = 26.5 ppm, 1 J RhP = 168.0 Hz, 2 J PP = 55.6 Hz) along with the phosphonium P atom (δ P = 37.5 ppm, 2 J PP = 55.6 Hz). These chemical shifts and coupling constants are in line with values reported for structurally related complexes . The signal for the C-donor atom appears at 35.2 ppm in the 13 C­{ 1 H}-NMR spectrum as a ddd with coupling to both phosphorus atoms and the Rh­(I) center, and the peak for the ylide hydrogen atom appears at 4.46 ppm as a broad singlet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 31 P­{ 1 H}-NMR spectrum of 19 shows the presence of a Rh-coordinated phosphine (δ P = 26.5 ppm, 1 J RhP = 168.0 Hz, 2 J PP = 55.6 Hz) along with the phosphonium P atom (δ P = 37.5 ppm, 2 J PP = 55.6 Hz). These chemical shifts and coupling constants are in line with values reported for structurally related complexes . The signal for the C-donor atom appears at 35.2 ppm in the 13 C­{ 1 H}-NMR spectrum as a ddd with coupling to both phosphorus atoms and the Rh­(I) center, and the peak for the ylide hydrogen atom appears at 4.46 ppm as a broad singlet.…”
Section: Resultsmentioning
confidence: 99%
“…The ν CO in 20 was found to be 1984 cm −1 , and this value is comparable to, or lower than, CO stretching frequencies encountered in other related Rh(CO) carbene and ylide complexes 21−23 (Figure 5). 13,28,29 This indicates that ylide ligands derived from alkylidene dihydropyridine precursors retain the electron donating properties associated with other ylide ligands. Notably, the presence of a formally cationic N-methylpyridinium substituent on the ylide carbon does not appear to adversely affect ligand donor properties.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that the nitrogen substituent in the iminophosphorane group influences the electronic properties of the ligand. In this earlier study the isopropyl substituent enhances the electron donating ability of P=N group so that it almost equals that of the P + −CH 2 − containing ligand [11] …”
Section: Introductionmentioning
confidence: 85%
“…In this earlier study the isopropyl substituent enhances the electron donating ability of P=N group so that it almost equals that of the P + À CH 2 À containing ligand. [11] This influence has not been investigated previously because the nature of the substituent is generally dictated by how the P=N linkage is formed. Indeed, the Staudinger reaction is generally conducted with stable azides which feature a trimethylsilyl, a (thio)phosphonate, a bulky adamantyl, or an aryl group (Scheme 2i).…”
Section: Introductionmentioning
confidence: 99%